Identification of Variants Associated With Rare Hematological Disorder Erythrocytosis Using Targeted Next-Generation Sequencing Analysis - Kristan, Aleša; Pajič, Tadej; Maver, Aleš; Režen, Tadeja; Kunej, Tanja; Količ, Rok; Vuga, Andrej; Fink, Martina; Žula, Špela; Podgornik, Helena; Anžej Doma, Saša; Preložnik Zupan, Irena; et al. (Frontiers in Genetics, 2021)
An erythrocytosis is present when the red blood cell mass is increased, demonstrated as elevated hemoglobin and hematocrit in the laboratory evaluation. Congenital predispositions for erythrocytosis are rare, with germline variants in several genes involved in oxygen sensing (VHL, EGLN1, EPAS1), signaling for hematopoietic cells maturation (EPOR, EPO) and oxygen transfer (HBB, HBA1, HBA2, BPGM) that were already associated with the eight congenital types (ECYT1-8). Screening for variants in known congenital erythrocytosis genes with classical sequencing approach gives a correct diagnosis for only up to one-third of the patients. The genetic background of erythrocytosis is more heterogeneous and additional genes involved in erythropoiesis and iron metabolism could have a putative effect on the development of erythrocytosis. This study aimed to detect variants in patients with yet unexplained erythrocytosis using the NGS approach targeting genes associated with erythrocytosis and increased iron uptake and implement the diagnostics of congenital erythrocytosis in Slovenia. Selected 25 patients with high hemoglobin, hematocrit and no acquired causes were screened for variants in the 39 candidate genes. We identified one pathogenic variant in the EPAS1 gene and three novel variants with yet unknown significance in the genes EPAS1, JAK2 and SH2B3. Interestingly, a high proportion of patients were heterozygous carriers for two variants in the HFE gene, otherwise pathogenic for the condition of iron overload. The association between the HFE variants and the development of erythrocytosis is not clearly understood. With a targeted NGS approach, we determined an actual genetic cause for the erythrocytosis in one patient and contributed to better management of the disease for the patient and his family. The effect of variants of unknown significance on the enhanced production of red blood cells needs to be further explored with functional analysis. This study is of great significance for the improvement of diagnosis of Slovenian patients with unexplained erythrocytosis and future research on the etiology of this rare hematological disorder.